# x^2+12x+33=0

## Simple and best practice solution for x^2+12x+33=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for x^2+12x+33=0 equation:

Simplifying x^{2}+ 12x + 33 = 0 Reorder the terms: 33 + 12x + x^{2}= 0 Solving 33 + 12x + x^{2}= 0 Solving for variable 'x'. Begin completing the square. Move the constant term to the right: Add '-33' to each side of the equation. 33 + 12x + -33 + x^{2}= 0 + -33 Reorder the terms: 33 + -33 + 12x + x^{2}= 0 + -33 Combine like terms: 33 + -33 = 0 0 + 12x + x^{2}= 0 + -33 12x + x^{2}= 0 + -33 Combine like terms: 0 + -33 = -33 12x + x^{2}= -33 The x term is 12x. Take half its coefficient (6). Square it (36) and add it to both sides. Add '36' to each side of the equation. 12x + 36 + x^{2}= -33 + 36 Reorder the terms: 36 + 12x + x^{2}= -33 + 36 Combine like terms: -33 + 36 = 3 36 + 12x + x^{2}= 3 Factor a perfect square on the left side: (x + 6)(x + 6) = 3 Calculate the square root of the right side: 1.732050808 Break this problem into two subproblems by setting (x + 6) equal to 1.732050808 and -1.732050808.## Subproblem 1

x + 6 = 1.732050808 Simplifying x + 6 = 1.732050808 Reorder the terms: 6 + x = 1.732050808 Solving 6 + x = 1.732050808 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + x = 1.732050808 + -6 Combine like terms: 6 + -6 = 0 0 + x = 1.732050808 + -6 x = 1.732050808 + -6 Combine like terms: 1.732050808 + -6 = -4.267949192 x = -4.267949192 Simplifying x = -4.267949192## Subproblem 2

x + 6 = -1.732050808 Simplifying x + 6 = -1.732050808 Reorder the terms: 6 + x = -1.732050808 Solving 6 + x = -1.732050808 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + x = -1.732050808 + -6 Combine like terms: 6 + -6 = 0 0 + x = -1.732050808 + -6 x = -1.732050808 + -6 Combine like terms: -1.732050808 + -6 = -7.732050808 x = -7.732050808 Simplifying x = -7.732050808## Solution

The solution to the problem is based on the solutions from the subproblems. x = {-4.267949192, -7.732050808}

### See similar equations:

| 7x-9=15+4x | | -x^2-4x-3=0 | | -x^2-3x+18=0 | | .6(d+3)=3d | | -x^2-4X=0 | | -7x^2+52x-85=0 | | 6x+9=-17-7x | | 7-9x=36-13x | | 57-2x=7x+23 | | 13x-147=6x-14 | | 4x+7=3x-1 | | -6x^2-17X+28=0 | | 2(5x+3)=12x+3 | | 3y=2x+6 | | 5x+10Y=50 | | 9-3x-15=30 | | 2+W=5 | | 4x^2+26x+30=0 | | -2y+-12=y+3+2y | | -.006x^2+1.2x+10=0 | | m-38=-44 | | 4x+6=-3x+-15 | | 3x-10=-4x+60 | | 5x^2-6x-7=0 | | 8x-60=4x-20 | | 6x+46=73 | | 5x-2=12x-58 | | n+13=-5 | | 4x-15=89 | | 2w-6=64 | | 2w+6=70 | | 2w+6=76 | | x+32=33 | | 2(35-3)+6=70 | | 9x+8=7x+18# | | 3.2x+x=1.2 | | b-37=-54 | | ln(x-1)+ln(x+1)=0 | | 7x^3-2x=0 | | 9(b-4)-7b=5(b-2) | | r-44=2 | | 7a+16-3a-7=-11 | | 105-3x=5x+9 | | n+26=-23 | | 6x+9=-141-9x | | x-31=-61 | | 14-8x=51-15x | | 9x-4=4x+1 | | 4x+8=2x-12 | | 4x+17=14x-73 | | 2-2(n-2)-3n=21+7 | | 9x^2-18x+3=0 | | a+39=72 | | y=6x-10x+8 | | 8x-118=3x-13 | | 6x+30=16x-90 | | 7+x=2x+14 | | v-6=9 | | x-7=33 | | -46-4x=14-10x | | x^3+1= | | 37+x=58 | | 108-5x=3x+20 | | 15-(2-3x)=4x | | 7+x=-2x+14 |